2020
DOI: 10.1016/j.psj.2020.01.024
|View full text |Cite
|
Sign up to set email alerts
|

The effects of lignocellulose supplementation on laying performance, egg quality parameters, aerobic bacterial load of eggshell, serum biochemical parameters, and jejunal histomorphological traits of laying hens

Abstract: This study was performed to investigate the effects of lignocellulose supplementation ( LS ) on performance parameters, egg quality, aerobic bacterial load of eggshell, serum biochemical parameters, and jejunal histomorphological traits of laying hens between 18 and 38 wk of age. A total of 640 pullets at 16 wk of age were allotted to 4 treatment groups as 0 kg (control, CONT ), 0.5 kg, 1 kg, and 2 kg LS per ton of feed. Body weight ( BW ), d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
8
1
Order By: Relevance
“…With respect to feeding experiments with commercial hybrid pullets and laying hens (Table 3 ), most studies showed that growth and laying performance were not affected by dietary LC inclusion levels of 0.8% to 2% [ 33 – 35 ]. However, Sozcu and Ipek [ 36 ] demonstrated that the supplementation of 0.05% and 0.1% dietary LC increased BW, ADFI, EP, and EW of laying hens between 18 to 38 weeks of age compared to hens fed the control diet. A further increase in the dietary LC concentration to 0.2%, however, led to a decrease in EP and EW [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to feeding experiments with commercial hybrid pullets and laying hens (Table 3 ), most studies showed that growth and laying performance were not affected by dietary LC inclusion levels of 0.8% to 2% [ 33 – 35 ]. However, Sozcu and Ipek [ 36 ] demonstrated that the supplementation of 0.05% and 0.1% dietary LC increased BW, ADFI, EP, and EW of laying hens between 18 to 38 weeks of age compared to hens fed the control diet. A further increase in the dietary LC concentration to 0.2%, however, led to a decrease in EP and EW [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, Sozcu and Ipek [ 36 ] demonstrated that the supplementation of 0.05% and 0.1% dietary LC increased BW, ADFI, EP, and EW of laying hens between 18 to 38 weeks of age compared to hens fed the control diet. A further increase in the dietary LC concentration to 0.2%, however, led to a decrease in EP and EW [ 36 ]. In two other studies, the effect of dietary LC was investigated in broiler breeder hens [ 37 ] during the laying phase (43 to 55 weeks of age) and in dual purpose hens [ 38 ] during the growing (1–22 weeks of age) and laying period (23–52 weeks of age).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the villus height-to-crypt depth ratio (VH/CD), which is a measure of the epithelial cell turnover [41], was lower in the control group for the three small intestine tracts. Sozcu and Ipek [43] studied the effects of lignocellulose supplementation on jejunal histomorphology of laying hens, including increasing levels (0.05, 0.1, and 0.2 g/100 g feed) of a commercial product containing 92.6 g of ADL per 100 g. The authors observed that lignocellulose at 0.05 and 0.1% improved jejunum mucosal development by increasing villus height and VH/CD ratio, and such a result is in agreement with our findings, since the ADL in the AG group was 0.14% higher than the control. The villus size (height and width) is fundamental for the absorptive activity of the intestine [44].…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, layer hen cecal microbiota is capable of fermenting forages such as alfalfa ( Ricke et al., 2013 ). Sozcu and Ipek (2020) examined a lignocellulose product supplemented in feed for layer hens housed in enriched layer cages with perches, nesting areas, and scratch pads. When added at one gram per ton of feed, several egg production parameters were enhanced, including egg production, weight, quality, immunoglobulin levels, and intestinal architecture.…”
Section: Prebiotics and Alternative Egg Production Systemsmentioning
confidence: 99%